The relationship between emotional intelligence and job satisfaction at Pejabat Majlis Daerah, Besut, Terengganu/ Anis Suhaila Alwi - Alwi, Anis Suhaila (2017)
The main purpose of this study is to examine the relationship between emotional intelligence and job satisfaction among support staff at Pejabat Majlis Daerah, Besut, Terengganu. The instrument that was used to collect the data was questionnaire. This study was correlational research. 120 sets of questionnaire were distributed to the respondents personally with return rate of 94.2%. The data was analyzed using the Statistical Package for Social Science Software (SPSS) version 23.0. Pearson correlation was performed on the data in order to determine whether there is a relationship between emotional intelligence and job satisfaction. The findings show that there is a strong relationship between both variables. The correlation values show that emotional intelligence have strong relationship with job satisfaction. There is a significant strong positive and high correlation (r = .505, p<0.01) between job satisfaction and self-awareness. There is a significant positive and medium relationship between job satisfaction with self-management and social awareness with (r = .473, p<0.01 and r =.351, p<0.01). There is a significant positive and small correlation (r = .197, p<0.05) between job satisfaction and relationship management. Researcher recommends that the future research should be expended to other location rather than Besut only.